Core‐Shell Nanoparticles with a Redox Polymer Core and a Silica Porous Shell as High‐Performance Cathode Material for Lithium‐Ion Batteries. Issue 3 (9th March 2020) - Jia, He; Friebe, Christian; Schubert, Ulrich S.; Zhang, Xiaozhe; Quan, Ting; Lu, Yan; Gohy, Jean-François
Abstract : Core‐shell nanoparticles are fabricated based on a redox polymer core and a porous SiO2 shell and embedded homogeneously into carbon nanotubes conductive networks. Due to the uniform dispersion of active units, the resulting free‐standing composite electrode exhibits a high specific capacity at 10C and a long cycling life. More details can be found in article number 1901040 by He Jia, Jean‐François Gohy, and co‐workers.